2018
DOI: 10.1007/s11605-017-3641-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frailty Index on Early Outcomes after Combined Colorectal and Liver Resections

Abstract: The 5-item mFI is significantly associated with 30-day morbidity in patients undergoing combined colorectal and liver resections. It is a tool that can guide surgeons preoperatively in assessing morbidity risk in patients undergoing concomitant resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
1
43
0
1
Order By: Relevance
“…We also found that patients with higher frailty scores were more likely to have open surgery. This is despite multiple studies reporting that higher morbidity is associated with the open compared to the minimally invasive approach [25,[27][28][29] and that the laparoscopic approach is protective against intensive care unit level complications in colectomy patients [10]. Known attributes of laparoscopic surgery, such as smaller incisions, less intra-operative blood loss, shorter LOS and faster recovery might dilute the magnitude of the physiological stress associated with a colectomy [25,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that patients with higher frailty scores were more likely to have open surgery. This is despite multiple studies reporting that higher morbidity is associated with the open compared to the minimally invasive approach [25,[27][28][29] and that the laparoscopic approach is protective against intensive care unit level complications in colectomy patients [10]. Known attributes of laparoscopic surgery, such as smaller incisions, less intra-operative blood loss, shorter LOS and faster recovery might dilute the magnitude of the physiological stress associated with a colectomy [25,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . examined the impact of 5‐mFI scores on 1928 patients who had combined liver and colon resections and reported mFI ≥ 2 to be significantly associated with increased odds of overall and serious morbidity. Vermillion et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rFI scores were significantly associated with postoperative complications, prolonged LOS, and mortality, while higher mFI scores were linked only to a higher risk of morbidity but neither mortality nor LOS [49] . Chen et al [69] evaluated the use of a five-item mFI to assess the effect of frailty on outcomes in patients undergoing combined colorectal and liver resection for colorectal cancer and liver metastases. Patients with higher mFI scores exhibited a higher incidence of mortality, overall and severe morbidity, as well as prolonged LOS.…”
Section: Liver Resection and Frailtymentioning
confidence: 99%
“…While clinical decision support (CDS) has permeated medical care, there are few surgical CDS tools to predict resource utilization. Most work has been specialty and/or procedure specific 9 or has addressed questions of comparative effectiveness. 10 , 11 The role of predictive analytics in improving operating room efficiency has been touted for day-of-staffing and resource-allocation decisions.…”
Section: Introductionmentioning
confidence: 99%